Multimodal signal processing theory and applications for human-computer interaction - Thiran, Jean-Philippe (EURASIP and Academic Press series in signal and image processing., 2010)
Presents state-of-art methods for multimodal signal processing, analysis, and modeling Contains numerous examples of systems with different modalities combined Describes advanced applications in multimodal Human-Computer Interaction (HCI) as well as in computer-based analysis and modelling of multimodal human-human communication scenes. Multimodal signal processing is an important research and development field that processes signals and combines information from a variety of modalities - speech, vision, language, text - which significantly enhance the understanding, modelling, and performanc.